FORMULASI PRODUK SUSU FERMENTASI KERING DENGAN PENAMBAHAN BAKTERI PROBIOTIK Lactobacillus casei DAN Bifidobacterium longum - Dida Hani Rahman; Ikeu Tanziha; Sri Usmiati (Jurnal Gizi dan Pangan, 2012)
Fermented milk is a healthy product that has many benefits especially for human digestive tract. Manufacturing of probiotic fermented milk products as a functional food with a viable long shelf life needs to be developed. The purpose of this study was to formulate a dried fermented milk product using probiotic bacterias. The experimental design study was a complete random design with 4 treatments using different lactic acid bacteria (LAB): A1 (Streptococcus lactis: 0.5%); A2 (Streptococcus lactis: 0.25% and Lactobacillus casei: 0.25%); A3 (Streptococcus lactis: 0.25%, Lactobacillus bulgaricus: 0.125%, Streptococcus thermophiles: 0.125%); and A4 (Streptococcus lactis: 0.25% and Bifidobacterium longum: 0.25%). The highest level of hardness was A2 product and the highest level of tenderness is A1 product. Results of proximate analysis showed that dried fermented milk products had high levels of the protein, calcium, and phosphorus. Microbiological test results showed that the amount of lactic acid bacteria (BAL) in dried fermented milk products were eligible based on CODEX: 243 (2003). Statictical analysis using ANOVA in the hedonic quality test showed that the treatments were significantly different (p 0.05) on the attributes of color, aroma, hardness, and flavor except texture.